(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The present study is conducted to understand the adoption of UPI (Unified Payments Interface) among rural people in India. Meta UTAUT (Unified Theory of Acceptance and Use of Technology) model is used to evaluate the critical factors. A well-structured questionnaire was distributed among 195 users of UPI in villages of Haryana and the data collected was analysed using PLS-SEM. A total of 13 hypotheses were proposed and 9 of them were accepted. Findings show that Social Influence (SI), Performance Expectancy (PE), Effort Expectancy (EE), and Facilitating Conditions (FC) have direct positive influence on Attitude whereas only PE & FC have direct effect on BI. Attitude fully mediates the effects of EE & SI on BI as they do not have direct significant impact on BI. Whereas, it partially mediates the impact of FC and PE on BI as they have direct as well as indirect effect on BI. On the other hand, direct influence of PE & FC on attitude is strong as compared to their direct influence on BI. The study explores the critical factors which influence the adoption of UPI among rural people and also discusses how this knowledge can be used to improve UPI adoption among rural people. UPI has provided newer digital payment avenue to both urban and rural consumers in India. However, adoption of UPI in rural India remains unexplored area. It is one of the pioneer studies in India context to explore the adoption of UPI among rural India.